Robotic colorectal surgery: experiences, challenges and opportunities through our own research - Igor Černi; Dragan Vanovac (Биомедицинска истраживања, 2024)
Robotic colorectal surgery has revolutionized minimally invasive surgical techniques, offering numerous advantages over traditional approaches. Enhanced precision, reduced blood loss, shorter hospital stays, and improved patient outcomes are among the key benefits. However, high costs and technical complexities limit its widespread adoption. This study explores the experiences, challenges, and future directions of robotic colorectal surgery. While it offers significant advantages, further research is needed to optimize techniques, reduce costs, and expand its application. By addressing technical limitations and exploring innovative approaches, robotic surgery has the potential to further improve patient care and surgical outcomes.
Keywords: robotic surgery; colorectal surgery; minimally invasive surgery; surgical outcomes; technological advancements